Creation of polymer microlens security elements with an optically varying effect - Tanin, Leonid V.; Harcharuk, Andrey I. (Journal of the Belarusian State University. Physics, 2024)
It is noted that optical security elements based on polymer microoptical systems are a promising platform for creating new visual features that can be used in technologies for protecting securities and documents. The physical principles of stereo and vario image formation using a microlens matrix are presented. It is shown that as a result of the complex interaction between an array of microlenses and an array of microimages, virtual synthesised images are formed, which shift when the viewing angle changes, i. e. floating images. Such images are used as a security feature. With the use of digital hologram recording technology, microimage arrays with high resolution have been obtained, which cannot be achieved using traditional printing techniques. A method has been developed to increase the contrast between areas containing microimages and blank film.
Keywords: holographic security element; hologram; optical system; microlens; microlens array; stereo effect; parallax; graphic image